High-intensity interval training versus continuous training on physiological and metabolic variables in prediabetes and type 2 diabetes: A meta-analysis. (March 2018) - De Nardi, Angélica Trevisan; Tolves, Tainara; Lenzi, Thatiane Larissa; Signori, Luis Ulisses; Silva, Antônio Marcos Vargas da
Highlights: HIIT induces cardiometabolic adaptations similar to MICT in prediabetes and T2D. HIIT provide greater benefits to functional capacity in patients with T2D. It is suggested more research to strengthen the quality of current evidence. Abstract: Aims: To compare the effects of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) on functional capacity and cardiometabolic markers in individuals prediabetes and type 2 diabetes (T2D). Methods: The search was performed in PubMed (MEDLINE), EMBASE, PEDro, CENTRAL, Scopus, LILACS database, and Clinical Trials from the inception to July 2017, included randomized clinical trials that compared the use of HIIT and MICT in prediabetes and T2D adults. The risk of bias was defined by Cochrane Handbook and quality of evidence by GRADE. Results: From 818 relevant records, seven studies were included in systematic review (64 prediabetes and 120 T2D patients) and five with T2D were meta-analyzed. HIIT promoted significantly increased of 3.02 mL/kg/min (CI95% 1.42–4.61) of VO2 max, measured for functional capacity, compared to MICT. No differences were found between two modalities of exercises considering the outcomes HbA1c, systolic and diastolic blood pressure, total cholesterol, HDL and LDL cholesterol, triglycerides, BMI, and waist-to-hip ratio. Most of the studies presented unclear risk of bias, and low and very low quality of evidence. Conclusion: HIIT induces cardiometabolic adaptations similar to those of MICT in prediabetes and T2D, and provides greater benefits to functional capacity in patients with T2D. PROSPERO: CRD42016047151.